Lung cancer among young patients in Dharmais Cancer Center Hospital, Jakarta (1994-1998) (Medical Journal of Indonesia, 2001)
Lung cancer is usually seen in patients of middle and old age. The disease is rarely seen in patients under 40 years. In Dharmais Cancer Center Hospital 37 patients of 40 years of age or younger were seen. The number was 5.9% of the total of lung cancer cases that was seen in this hospital in 1994 - 1998. The disease was more dominant among males (male to female ratio 3 : 1), age between 26-40 years. Most of the patients were stage IV (45.7%), chief complaints were dyspnea (58.I%) and pain (32.5%). Nonsmall cell carcinoma was the most frequent histologic type (91.9%), small sell carcinoma was seen in 2.7% and in 5.4% the histologic type could not be determined. The treatment consisted of surgery in 9 cases, radiotherapy in 17 cases and chemotherapy in 5 cases. Fourteen patients (38%) died in hospital, the rest were not followed further. (Med J Indones 2001; 10: 73-8) Keywords : lung cancer, young age